Enthusiasm for Introducing and Integrating HIV Self-Testing but Doubts About Users: A Baseline Qualitative Analysis of Key Stakeholders' Attitudes and Perceptions in Côte d'Ivoire, Mali and Senegal - Ky-Zerbo, Odette; Desclaux, Alice; Kouadio, Alexis Brou; Rouveau, Nicolas; Vautier, Anthony; Sow, Souleymane; Camara, Sidi Cheick; Boye, Sokhna; Pourette, Dolorès; Sidibé, Younoussa; Maheu-Giroux, Mathieu; Larmarange, Joseph (Frontiers in Public Health, 2021)
Since 2019, the ATLAS project, coordinated by Solthis in collaboration with national AIDS programs, has introduced, promoted and delivered HIV self-testing (HIVST) in Côte d'Ivoire, Mali and Senegal. Several delivery channels have been defined, including key populations: men who have sex with men, female sex workers and people who use injectable drugs. At project initiation, a qualitative study analyzing the perceptions and attitudes of key stakeholders regarding the introduction of HIVST in their countries and its integration with other testing strategies for key populations was conducted. The study was conducted from September to November 2019 within three months of the initiation of HIVST distribution. Individual interviews were conducted with 60 key informants involved in the project or in providing support and care to key populations: members of health ministries, national AIDS councils, international organizations, national and international nongovernmental organizations, and peer educators. Semi structured interviews were recorded, translated when necessary, and transcribed. Data were coded using Dedoose© software for thematic analyses. We found that stakeholders’ perceptions and attitudes are favorable to the introduction and integration of HIVST for several reasons. Some of these reasons are held in common, and some are specific to each key population and country. Overall, HIVST is considered able to reduce stigma; preserve anonymity and confidentiality; reach key populations that do not access testing via the usual strategies; remove spatial barriers; save time for users and providers; and empower users with autonomy and responsibility. It is noninvasive and easy to use. However, participants also fear, question and doubt users’ autonomy regarding their ability to use HIVST kits correctly; to ensure quality secondary distribution; to accept a reactive test result; and to use confirmation testing and care services. For stakeholders, HIVST is considered an attractive strategy to improve access to HIV testing for key populations. Their doubts about users’ capacities could be a matter for reflective communication with stakeholders and local adaptation before the implementation of HIVST in new countries. Those perceptions may reflect the West African HIV situation through the emphasis they place on the roles of HIV stigma and disclosure in HIVST efficiency.